Idiopathic calcinosis cutis of the penis - Ram Tainwala; Y K Sharma; Niti Gaur (Wolters Kluwer Medknow Publications, 2010)
Calcification of the skin occurs in four main forms namely dystrophic, metastatic, iatrogenic and idiopathic. Idiopathic calcinosis cutis of the penis is exceedingly rare as only five cases have been reported till date to the best of our knowledge. Herein, we present another case of this rare entity in a 29-year old man and discuss its probable pathogenic origin.